«DIGITAL RATING KFU» AN INTERACTIVE SYSTEM FOR ACCOUNTING AND ANALYSIS OF TEACHER RATINGS AT THE BRANCH OF KFU - Umarov Boburjon (Uzbekistan Open Conference, 2025)
The article describes the development and implementation of the Digital Rating KFU web system, designed to automate the accounting and analysis of the scientific activity of the teaching staff of the Jizzakh branch of Kazan (Volga Region) Federal University. The project is aimed at solving the problem of low efficiency of traditional reporting methods and increasing the motivation of scientific and pedagogical staff. The system architecture, applied technologies, and implementation results are presented. The role of digital tools in developing the university’s internal scientific culture and forming a transparent rating model is emphasized. The presented results demonstrate the possibilities of practical digital transformation of educational institutions.
Keywords: digitalization of education; scientific activity; teaching staff rating; accounting automation; information systems; Django; university analytics; educational technologies